Responses of Intestinal Mucosal Barrier Functions of Rats to Simulated Weightlessness - Jin, Mingliang; Zhang, Hao; Zhao, Ke; Xu, Chunlan; Shao, Dongyan; Huang, Qingsheng; Shi, Junling; Yang, Hui (Frontiers in Physiology, 2018)
Exposure to microgravity or weightlessness leads to various adaptive and pathophysiological alterations in digestive structures and physiology. The current study was carried out to investigate responses of intestinal mucosal barrier functions to simulated weightlessness, by using the hindlimb unloading rats model. Compared with normal controls, simulated weightlessness damaged the intestinal villi and structural integrity of tight junctions, up-regulated the expression of pro-apoptotic protein Bax while down-regulated the expression of anti-apoptotic protein Bcl-2, thus improved the intestinal permeability. It could also influence intestinal microbiota composition with the expansion of Bacteroidetes and decrease of Firmicutes. The predicted metagenomic analysis emphasized significant dysbiosis associated differences in genes involved in membrane transport, cofactors and vitamins metabolism, energy metabolism, and genetic information processing. Moreover, simulated weightlessness could modify the intestinal immune status characterized by the increase of proinflammatory cytokines, decrease of secretory immunoglobulin A, and activation of TLR4/MyD88/NF-κB signaling pathway in ileum. These results indicate the simulated weightlessness disrupts intestinal mucosal barrier functions in animal model. The data also emphasize the necessity of monitoring and regulating astronauts’ intestinal health during real space flights to prevent breakdowns in intestinal homeostasis of crewmembers.